2004
DOI: 10.1097/00129492-200403000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Superior Semicircular Canal Dehiscence Presenting as Conductive Hearing Loss Without Vertigo

Abstract: SSCD can present with a conductive hearing loss that mimics otosclerosis and could explain some cases of persistent conductive hearing loss after uneventful stapedectomy. Audiometric testing with attention to absolute bone-conduction thresholds, acoustic reflex testing, VEMP testing, laser vibrometry of the umbo, and computed tomograph scanning can help to identify patients with SSCD presenting with conductive hearing loss without vertigo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
283
3
17

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 286 publications
(329 citation statements)
references
References 14 publications
20
283
3
17
Order By: Relevance
“…We previously reported low-frequency increases in CP response to BC stimuli in chinchilla after the introduction of a SCD with a mean gain of 8.1 dB near 500 Hz . The increased sensitivity to BC in chinchilla is consistent with clinical observations of super-sensitive (<0 dB) BC thresholds in many patients with SCD syndrome (Minor et al, 2003;Mikulec et al, 2004) as well as those found in sandrat (Sohmer et al, 2004). At 500 Hz, the present study showed an 8.7 dB decrease in the chinchillas response to AC stimuli.…”
Section: Comparison To Clinical Studiessupporting
confidence: 92%
See 4 more Smart Citations
“…We previously reported low-frequency increases in CP response to BC stimuli in chinchilla after the introduction of a SCD with a mean gain of 8.1 dB near 500 Hz . The increased sensitivity to BC in chinchilla is consistent with clinical observations of super-sensitive (<0 dB) BC thresholds in many patients with SCD syndrome (Minor et al, 2003;Mikulec et al, 2004) as well as those found in sandrat (Sohmer et al, 2004). At 500 Hz, the present study showed an 8.7 dB decrease in the chinchillas response to AC stimuli.…”
Section: Comparison To Clinical Studiessupporting
confidence: 92%
“…These studies demonstrated that sensitivity to BC stimuli increases after the introduction of a dehiscence and that the increase is greatest at frequencies below 2 kHz . The increase in sensitivity to BC sound in animal models is consistent with the increased bone-conduction sensitivity (decreased thresholds) in some SCD patients (Minor et al, 2003;Mikulec et al, 2004) (Fig. 1).…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations